Fermentation-driven microbial and metabolic shifts in filler tobacco leaves of different grades - He, Chen; Yang, Shaoxin; Dong, Shengnan; Wang, Shengxiao; Zhang, Pengfei; Yang, Yang; Xu, Delong; Yang, Rongchao; Zeng, Bo; Hu, Yanqi; Zhang, Qing (Frontiers in Microbiology, 2025)
IntroductionFiller tobacco leaves (FTLs) serve as the primary raw material for cigar production, and notable differences in physicochemical properties and fermentation responsiveness exist across different grades. However, the underlying mechanisms governing microbial and metabolic evolution during FTL fermentation remain poorly understood. This study systematically investigated the microbial community structures and metabolomic profiles of FTLs of varying grades before and after fermentation using metagenomic sequencing and untargeted metabolomics.ResultsMetagenomic analysis revealed marked differences in microbial composition among FTL grades at the onset of fermentation. The fermentation process further facilitated the enrichment of functional genera such as Bacillus, Escherichia, and Alternaria, while low-grade FTLs exhibited excessive accumulation of Corynebacterium, potentially contributing to off-flavors and undesirable odors. Untargeted metabolomics identified numerous significantly differential metabolites after fermentation, primarily enriched in pathways related to amino acid biosynthesis, sugar metabolism, and carotenoid biosynthesis. Principal component analysis and hierarchical clustering indicated partial continuity in metabolomic profiles within the same grade before and after fermentation. Correlation analysis further revealed strong positive associations between several dominant genera and flavor-related metabolites.ConclusionThis study demonstrates that FTLs of different grades exhibit distinct patterns of microbial succession and metabolic remodeling during fermentation. The initial leaf grade plays a pivotal role in shaping microbial communities and metabolite accumulation. These findings offer mechanistic insights into the fermentation process of FTLs and provide theoretical and practical guidance for optimizing raw material grading and fermentation management in the cigar industry.